Jus Post Bellum Restraint, Stabilisation and Peace. - Mileham, Patrick (International Studies on Military Ethics Ser., 2020)
"Jus Post bellum: Restraint, Stabilisation and Peace seeks to answer the question "is restraint in war essential for just, lasting peace"? With a foreword by Professor Brian Orend who asserts this as "a most commendable subject" in extending Just War Theory, the book contains chapters on the ethics of war-fighting since the end of the Cold War and a look into the future of conflict. From the causes of war, with physical restraint and reconciliation in combat and political settlement, further chapters written by expert academics and military participants cover international humanitarian law, practicalities of the use of force and some of the failures in achieving safe and lasting peace in modern-day theatres of conflict".